TINGKAT KEJADIAN TREMATODIASIS PADA TERNAK KAMBING - Zulkifli Husain; Tri Ananda Erwin Nugroho (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2021)
This study aims to determine the prevalence of trematodiasis in goats in Paguat and Randangan sub-districts, Pohuwato district in October-November 2019. Sampling was carried out proportionally randomly with a 90% confidence level of a population of 2966 tails at the village level. Faecal samples are collected through the rectum by rectal palpation and some are taken shortly after the defecation goat. Inspection of samples using native, depositional and floating methods. The results of the study were obtained from 93 goat faecal samples taken in Paguat District, 17 samples were found Trematoda worm eggs, while in Randangan District from 94 goat faecal samples were taken, as many as 14 samples were found Trematoda worm eggs. Thus the prevalence of trematodiasis in goats in Paguat District was 18% and Randangan District was 15%. The prevalence of Trematodiasis in Paguat District was obtained through negative examination of 4%, deposition of 9%, and floatation of 5%, while the prevalence of Trematodiasis in Randangan District was obtained through native examination of 5%, deposition of 7%, and floatation of 3%.